Synthesis and Characterization of Carbon Nanodots for Detection and Quantification of Ferric (III) Ions - Tan, Shao Chien (unimas, 2017)
In this research, green electrochemically synthesized Carbon Nanodots (C-Dots) and one-pot microwave synthesized Nitrogen-doped Carbon Nanodots (N-CDs) were studied as chemical sensor for detection of Ferric (Fe3+) ions. C-Dots were synthesized electrochemically through a green chemistry approach using spent battery carbon rods and ultrapure water. The C-Dots were used to modify Screen Printed Carbon Electrode (SPCE) through drop-coating method and the electrochemical properties were characterized using Cyclic Voltammetry (CV). The current intensity of the C-Dots modified SPCE was shown to improve significantly by 259% when compared to the unmodified SPCE. Various concentration of Fe3+ ions ranging from 0.5 to 25.0 ppm further enhanced the current intensity up to 734% when compared with unmodified SPCE, showing a trend of linear relationship. The SPCE electrochemical sensor strip exhibited a linear detection range of 0.5 to 25.0 ppm Fe3+ ions and the limit of detection (LOD) calculated was 0.44 ± 0.04 ppm (S/N ratio of 3).